Contributions of smart manufacturing in BERNAS to the regional development: Case study in Paya Keladi, Pulau Pinang - Mohamad Mahayudin, Nur Awanis; Samsurijan, Mohamad Shaharudin (Journal of Islamic, Social, Economics and Development, 2025)
The adoption of smart manufacturing technology has become a crucial driver for industrial transformation, particularly in the rice processing industry. This study explores the contributions of smart manufacturing in BERNAS Paya Keladi, Pulau Pinang to the regional development. By integrating automation, digital monitoring systems and data analytics, BERNAS has enhanced production efficiency, minimized operational cost and improved product quality. These advancements have not only benefited the company but have also had significant economic and social implications for the surrounding region. The study adopts a qualitative case study approach, utilizing interviews and observations to assess the impact of smart manufacturing on the local economy and workforce. Findings indicate that the implementation of smart manufacturing has led to increased job opportunities particularly in high-skilled positions while also necessitating reskilling initiatives for workers. Additionally, the technological improvements in rice processing have strengthened local supply chains, creating new business opportunities for small and medium enterprises (SMEs). Furthermore, the adoption of smart manufacturing practices has enhanced sustainability efforts by reducing waste and energy consumption contributing to the environmental well-being of the region. In conclusion, smart manufacturing in BERNAS Paya Keladi has positively impacted regional economic growth, and employment patterns and environmental sustainability. The study provides valuable insights for policymakers and industry stakeholders on leveraging smart technologies to promote sustainable industrial and regional development.